Estatuto sintático-semântico do verbo fazer no português escrito do Brasil. - RASSI, Amanda Pontes (2008)
This study proposes to examine the operation and uses of the verb to do in written texts the Portuguese of Brazil. The model adopted for the analysis is the Lexicon-Grammar (GROSS, 1975, 1981), under which all syntactic and semantic rules of a language can be described from their simple sentences. Theory of valences (Borba, 1996) recognizes the same principle, adding that there is a hierarchy among the constituents of the sentence and that in general, the central lexical item that selects every other element is the phrasal item lexical verb. Theories of the Lexicon-Grammar and provision, together with the notions of sign, meaning, value, text and gender, are the theoretical foundation of this research, both qualitative and quantitative, seeking not only the types of verb do, but, above all, their degree of recurrence in the corpus. The meanings and uses of the verb were taken to the texts that make up the Lazio-Ref, reference corpus Project Lazio-Web, organized and published by NILC USP (ALUÍSIO et al., 2004). Breaks, therefore, the assumption that all the Portuguese verbs undergo a continuum, ranging from full verb - which is the prototype - even a verb constituent expression crystallized, assuming as a verb support, vicarious, operator-causative, hiperverbo, among other classifications. To get to these classes and therefore the results, the analysis of the corpus followed the Transformational Model (Harris, 1964, 1968), applying transformational rules to simple phrases to determine their acceptability or unacceptability of the language. The analysis revealed recognize three interesting properties regarding the operation of the verb do in written Portuguese of Brazil: a) form is predominantly as a verb support, unlike many other verbs in Portuguese; b) classification is for a continuum and can not be described in terms of limit between one category and another, but in terms of boundaries, where two categories are mixed and interpose c) is one of the most productive verbs of the Portuguese language, which is explained by idea of linguistic struggling economy.